Silent night [large type] : a Spenser Holiday novel - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2013)
It's December in Boston, and Spenser is busy planning the menu for Christmas dinner. He's confronted in his office by a homeless boy named Slide who has found refuge with an organization named Street Business, which gives shelter and seeks job opportunities for the homeless and lost. Slide's mentor, Jackie Alvarez, is being threatened, but it's not a simple case of intimidation; the trail leads to a dangerous drug kingpin, whose hold on the at-risk community Street Business serves threatens not just the boys' safety and security, but their lives as well.